The Implementation of Portfolio Assessment in Indonesian Language Learning at Vocational High Schools - Wijayanti, Aurelia Rani; Boeriswati, Endry; Supriyana, Asep (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This literature-based study aims to examine the application of portfolio assessment in Indonesian language learning at vocational high schools (SMK). The study reviews relevant research articles, books, and policy documents to describe how portfolio assessment is implemented in classroom settings, what strategies are used, and what outcomes are achieved. Findings show that the implementation of portfolio assessment in SMK involves collecting student work over time, using it as a basis for reflection, feedback, and evaluation. This method supports active learning, encourages student independence, and aligns with the principles of meaningful and process-based assessment in language education. However, its application still faces several challenges, such as the need for teacher training, time allocation, and assessment standardization. This article contributes to the field of Indonesian Language and Literature Education by providing practical insights into how portfolio assessment can be effectively applied to improve teaching and learning processes in the vocational school context.